Tests of some insecticides against Tetranychus telarius Linnaeus (Tetranychyidae: Acarina) infesting brinjal in West Bengal. - Basu, A. C.; Pramanik, L. M. (Contributions to Entomology = Beiträge zur Entomologie, 1965)
The vegetable mite, Tetranychus telarius Linnaeus, is gradually assuming importance as a major pest of brinjal plant in West Bengal. - Three insecticides - Malathion, Thiodan and Trithion in different doses were tested for their efficacy in controlling the mite. - In general, all the chemicals, in doses tried, gave good results in the reduction of mite population by showing quick knock down activity and residual persistence for the period of test. - Trithion was found to be the most effective material and needs further investigation to find out an economic dose. The other insecticides were also fairly effective and gave adequate control.